2018
DOI: 10.1101/325688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New mitochondrial primers for metabarcoding of insects, designed and evaluated using in silico methods

Abstract: 1!Insect metabarcoding has been mainly based on PCR amplification of short fragments 2! within the 'barcoding region' of the gene COI. However, because of the variability of 3! this gene, it has been difficult to design good universal PCR primers. Most primers 4! used today are associated with gaps in the taxonomic coverage or amplification biases 5! that make the results less reliable and impede the detection of species that are present 6! in the sample. We identify new primers for insect metabarcoding using … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Former studies showed that hymenopteran sequences tend to have a lower affinity to universal COI primers compared to other arthropod groups 23 . In this study, only one COI primer pair was used which could have impaired the amplification of problematic arthropod groups such as Hymenoptera but also the Acari and Collembola due to primer bias and the use of target taxon-specific primers could have circumvented this 31 . The European web-spinning larch sawfly, Cephalcia lariciphila was found in soil samples taken at the pure spruce sites in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies showed that hymenopteran sequences tend to have a lower affinity to universal COI primers compared to other arthropod groups 23 . In this study, only one COI primer pair was used which could have impaired the amplification of problematic arthropod groups such as Hymenoptera but also the Acari and Collembola due to primer bias and the use of target taxon-specific primers could have circumvented this 31 . The European web-spinning larch sawfly, Cephalcia lariciphila was found in soil samples taken at the pure spruce sites in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Supplementary Figure S1, we then performed metabarcoding on each arthropod sample, with a two-step DNA amplification and high-throughput sequencing method adapted from the procedure described by Galan et al (2017). We sequenced three short COI fragments, with primer combinations and PCR protocols developed elsewhere (HCO forward: Leray et al 2013, HCO reverse: Folmer et al 1994, LEP F. and R.: Brandon-Mong et al 2015, HEX F. and R.: Marquina et al 2019), to overcome the problem of the lack of primer universality among arthropods. Error-proof indices for individual sample identification were developed with the high-throughput sequencing process described by Martin (2019).…”
Section: Methodsmentioning
confidence: 99%
“…We view this critical mass, which is complemented by various national‐level efforts, as a solid platform for the development of a terrestrial arthropod module, where passive sampling methods (e.g., pitfall, light and malaise traps, the last of which is already standardized within the BIOSCAN initiative) can be implemented individually, or in combination. Recent efforts toward developing best practices for COI community metabarcoding (e.g., Andújar et al, 2018; Elbrecht et al, 2019; Marquina et al, 2019) can be further developed for harmonized protocols for subsequent sample processing.…”
Section: A Framework For Harmonized Data Generation Within a Spatiallmentioning
confidence: 99%